New methodology for evaluation of non-pilot relay distance protection - Campos, João T. L. S. (2020)
Distance relays are typically used in transmission line protection. Their accuracy depends on the correct relay parameterization, phasor estimators, and correct usage of distance characteristics. Identifying suitable relay parameterization and algorithms considering multiple transmission line with various topologies and different fault types is a hard task. Here, a methodology based on the relay trip performance is proposed to evaluate all the main concerns of distance protection such as: maloperation trips per relay units in each fault type, overreach operation, and maloperation due to faults closer to the relay. The methodology could identify the best phasor estimators and distance configurations among those evaluated, as well as it could verify the power system topologies which yield in challenges for distance protection. The results achieved by the proposed methodology demonstrated that it can be useful for assisting the development of phasor estimators and new distance characteristics, as well as for setting existing distance protection in specific power system topologies